International projects as a new form of collaboration in the sphere of expert ensuring of justice - Kliuiev, Oleksandr; Agapova, Olena; Palkova, Karina (Archives of Criminology and Forensic Sciences, 2020)
In the article some statements ofIn the article the participation of the National Science Center «Hon. Prof. M. S. Bokarius Forensic Science Institute» in the bilateral research project was elucidated. It had been emphasized that the participation in the projects of the international cooperation is a new form of interaction of institutions of forensic activity that promote a development of the sphere of expert ensuring of justice. The regulatory and legal enactments of Ukraine and the Republic of Latvian, which regulate the participation’ question of scientists in fundamental and applied international research projects were analyzed. It is noticed that, Riga Stradins University and the National Science Center «Hon. Prof. M. S. Bokarius Forensic Science Institute» are participants of Joint Scientific Research Project. The content of the Ukrainian-Latvian project on the topic «Open Educational Resource: Forensic Science» is revealed that was devoted to the complex research of modern scientific approaches, the formation of theoretical regulations and practical summaries, related to the improvement of implementation of educational and scientific activity’s mechanisms of modern scientific approaches in the field of expert ensuring of justice Within the framework of the scientific project particular topical issues in forensic science are proposed to resolved. As a result of work on the project it is planned to publish scientific works, an open web-resource containing scientific, research and other materials, and also educational video presentations of work of the forensic expert with a possibility of their remote use is created. It was proved that the participation of domestic institutions within international projects assists the integration to European Higher Education Area and European Forensic Science Area.